Tectonics of the South Okhotsk deep-sea basin - Gnibidenko Helios S.; Svarichevsky Alexander S. (My University, 1984)
The South Okhotsk deep-sea basin is a morphologically-simple, fault-bounded basin located in the Kuril back-arc region.The structure of the crust is distinguished by three principal units: layer 1 (Vp ∼- 2–4 km/sec) is a layer of sediments 3–4 km thick. Layer 2 (Vp ∼- 4.5–5 km/sec) has a thickness of 0.5–1.5 km. Layer 3 (Vp ∼- 6.5–7 km/sec) is about 5 km thick, and has a probable basaltic to gabbroic composition. To a depth of 30 km, the upper mantle beneath the basin consists of alternating layers having velocities of 8.0 and 7.0 km/sec (Starshinova, 1980), which may be indicative of localized partial melting. Heat flow values are 2–2.5 times higher than normal. Sedimentation rates of 5–15 m/Ma for a thick, “transparent” sedimentary unit probably consisting of clays and argillites, and immediately overlying basement, suggest that sedimentation in the basin began in pre-Cretaceous time. There is no evidence of a ridge or rift in the basin, and the overlying sediments are undeformed. It is thus difficult to relate the formation of the South Okhotsk basin to subduction of the Pacific plates along its eastern margin.
Keywords: Берга (7.6)